Assessing diversity in canopy architecture, photosynthesis, and water‐use efficiency in a cowpea magic population. (7th August 2020) - Digrado, Anthony; Mitchell, Noah G.; Montes, Christopher M.; Dirvanskyte, Paulina; Ainsworth, Elizabeth A.
Abstract: Optimizing crops to improve light absorption and CO2 assimilation throughout the canopy is a proposed strategy to increase yield and meet the needs of a growing population by 2050. Globally, the greatest population increase is expected to occur in Sub‐Saharan Africa where large yield gaps currently persist; therefore, it is crucial to develop high‐yielding crops adapted to this region. In this study, we screened 50 cowpea ( Vigna unguiculata (L.) Walp) genotypes from the multi‐parent advanced generation inter‐cross (MAGIC) population for canopy architectural traits, canopy photosynthesis, and water‐use efficiency using a canopy gas exchange chamber in order to improve our understanding of the relationships among those traits. Canopy architecture contributed to 38.6% of the variance observed in canopy photosynthesis. The results suggest that the light environment within the canopy was a limiting factor for canopy CO2 assimilation. Traits favoring greater exposure of leaf area to light such as the width of the canopy relative to the total leaf area were associated with greater canopy photosynthesis, especially in canopies with high biomass. Canopy water‐use efficiency was highly determined by canopy photosynthetic activity and therefore canopy architecture, which indicates that optimizing the canopy will also contribute to improving canopy water‐use efficiency. We discuss different breeding strategies for future programs aimed at the improvement of cowpea yield for the Sub‐Saharan African region. We show that breeding for high biomass will not optimize canopy CO2 assimilation and suggest that selection should include multiple canopy traits to improve light penetration. Abstract : In this study, 50 cowpea ( Vigna unguiculata (L.) Walp) genotypes from the multi‐parent advanced generation inter‐cross (MAGIC) population were screened for canopy architectural traits, canopy photosynthesis, and water‐use efficiency using a canopy gas exchange chamber in order to improve our understanding of the relationship among those traits. Traits favoring greater exposure of leaf area to light such as the width of the canopy relative to the total leaf area were associated with greater canopy photosynthesis, especially in canopies with high biomass. Canopy water‐use efficiency was highly determined by canopy photosynthetic activity and therefore canopy architecture, which indicates that optimizing the canopy will also contribute to improving canopy water‐use efficiency.